Designing a Knowledge Management System Language Course Using SECI Model and RAD - Yuni Sugiarti; Haniya Nadira; An Nisa Ramadhanti (Compiler, 2026)
This research aims to design an efficient Knowledge Management System (KMS) by applying the Rapid Application Development (RAD) method and integrating the SECI model in the context of a language course. The study emphasizes the need for a fast and iterative development process to enhance the transfer of knowledge and improve learning outcomes. The approach focuses on combining the strengths of RAD's rapid prototyping with the SECI model, which supports knowledge sharing and internalization among learners. The method used includes the design and implementation of a web-based KMS to facilitate the exchange of knowledge between instructors and students. The findings indicate that the integration of RAD and the SECI model successfully improves the effectiveness of the KMS in enhancing learning experiences. The study concludes that a well-designed KMS can significantly support knowledge transfer and improve educational quality in language courses.